2008
DOI: 10.1021/ic802044r
|View full text |Cite
|
Sign up to set email alerts
|

Oxotechnetium(V) Complexes with a Novel Class of Tridentate Thiosemicarbazide Ligands

Abstract: A novel tridentate thiosemicarbazide-type ligand class with an SNS donor set, H(2)L(1), was prepared by reactions of N-[N',N'-dialkylamino(thiocarbonyl)]benzimidoyl chlorides with thiosemicarbazides. H(2)L(1) ligands readily react with (NBu(4))[TcOCl(4)] in MeOH under the formation of red oxotechnetium(V) complexes of composition [TcOCl(L(1))]. The monomeric, five-coordinate compounds are air-stable and bind (L(1))(2-) tridentate in the equatorial coordination sphere. The compounds represent the first examples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 15 publications
3
30
1
Order By: Relevance
“…2). Thus the bonding situation in the solid state of compound 14 recommends that it is treated as a ''hydrazide'' rather than a ''hydrazone'', as reported before for thiosemicarbazone/thiosemicarbazide compounds [19].…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…2). Thus the bonding situation in the solid state of compound 14 recommends that it is treated as a ''hydrazide'' rather than a ''hydrazone'', as reported before for thiosemicarbazone/thiosemicarbazide compounds [19].…”
Section: Resultsmentioning
confidence: 83%
“…The in vitro anti-M. tuberculosis properties of the synthesized thiosemicarbazones, semicarbazones, dithiocarbazates and hydrazide/hydrazones (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) were evaluated against M. tuberculosis H 37 Rv ATCC 27294 and the results for the Minimum Inhibitory Concentrations (MICs) are reported in Table 1. By investigating a series of thiosemicarbazones derived from 2-acetylpyridine it was observed that the substitution of one hydrogen atom linked to N(4) in the thiosemicarbazone moiety by various groups caused an improvement in their activities.…”
Section: Resultsmentioning
confidence: 99%
“…The non‐equivalence of the protons in the ethyl chain is due to a hindered rotation around the C–N bond, which has a partial double bond character. This is frequently observed for complexes with this class of ligands . Each non‐equivalent ligand generates two multiplets, corresponding to the two methylene groups.…”
Section: Resultsmentioning
confidence: 60%
“…They can deprotonate once or twice affording very flexible charge compensation of the metal ion. Besides, the high degree of electronic delocalisation in the ligand affords an efficient distribution of the negative charge all over the system, yielding stability . The organic residues can easily be functionalized and some of their metal complexes show promising anti‐parasitic activity …”
Section: Introductionmentioning
confidence: 99%
“…Recently, we extended the well-known coordination chemistry of bidentate ligands of this type [3], to novel tridentate N-[(dialkylamino)(thiocarbonyl)]benzamidines and studied their coordination behavior towards oxorhenium(V) and oxotechnetium(V) cores [3][4][5][6][7]. This also includes benzamidines derived from amino acids and amino acid esters, and we could demonstrate that ester hydrolysis of the corresponding glycine derivative (HL(GlyEt)) occurs during the reaction with the common oxorhenium(V) precursor [ReOCl 3 (PPh 3 ) 2 ] and finally a neutral rhenium(V) complex of the composition [ReOCl(PPh 3 ){L(Gly)}] with a equatorially coordinated {L(Gly)} 2À ligand is formed [4].…”
Section: Introductionmentioning
confidence: 99%